LINC00240/miR-155 axis regulates function of trophoblasts and M2 macrophage polarization via modulating oxidative stress-induced pyroptosis in preeclampsia - Hai-Ying Wu; Kan liu; Jing-Li Zhang (BMC, 2022)
Abstract Background This study aimed to investigate the effects of LINC00240/miR-155/Nrf2 axis on trophoblast function and macrophage polarization in the pathogenesis of preeclampsia. Methods Bindings between LINC00240, miR-155 and Nrf2 were validated by dual luciferase reporter assay or RNA-immunoprecipitation. Cell proliferation, migration, invasion, and pyroptosis were detected by CCK-8, clone formation, wound healing, Transwell system, and flow cytometry, respectively. Macrophage polarization was tested by flow cytometry. The expression levels of LINC00240, miR-155, Nrf2, and oxidative stress and pyroptosis-related markers in in vitro and in vivo preeclampsia models were analyzed by qPCR, western blot, or ELISA assays. Blood pressure, urine protein levels, liver and kidney damages, and trophoblast markers in placenta tissues were further studied in vivo. Results Placenta tissues from preeclampsia patients and animals showed decreased LINC00240 and Nrf2 and increased miR-155 expression levels, and the decreased M2 macrophage polarization. LINC00240 directly bound and inhibited expression of miR-155, which then inhibited oxidative stress-induced pyroptosis, promoting proliferation, migration and invasion abilities of trophoblasts, and M2 macrophage polarization. Inhibition of miR-155 led to increased Nrf2 expression and similar changes as LINC00240 overexpression in trophoblast function and macrophage polarization. Overexpression of LINC00240 in in vivo preeclampsia model decreased blood pressure, urine protein, liver and kidney damages, increased fetal weight and length, and induced trophoblast function and M2 macrophage polarization. Conclusion LINC00240 inhibited symptoms of preeclampsia through regulation on miR-155/Nrf2 axis, which suppressed oxidative stress-induced pyroptosis to improve trophoblast function and M2 macrophage polarization. LINC00240 could be a potential therapeutic target for preeclampsia.